Food Area Management “Mataba Puyud” Pattani Province to Develop Identity, Promote and Create Value of Marketing to Build Community Enterprises - Phuyuthanon, Ina (Journal of Humanities and Social Sciences Thonburi University, 2023)
The objectives of this research are 1) to utilize a local cuisine called Mataba to investigate and evaluate community identity in Puyud, Pattani, 2) to employ a video installation to encourage neighborhood engagement and 3) to assist and promote the business community. This qualitative research collects data through the examination of documents, in-depth interviews, and community team. The results showed that the historical structure in the community prior to the process of community identity art form had an impact on the development of tourism attractions with a public relation that was unique from the news tradition of the disturbance in the three southern provinces. The result has been an important indicator for the paranoid area, which has been long dominated by violence since 2004 by the news organization that presented a biased media depiction of people. The artistic activities that take place in this research will be a crucial mechanism that strengthens communities by extending to community collaboration with locals who have a variety of cuisine, arts, and culture identities outside of the broad sphere of religion.